Expression of the chemokine receptor CXCR2 in normal and neoplastic neuroendocrine cells - (:unkn) unknown (COLLEGE AMER PATHOLOGISTS, 2000)
Background-Chemokines effect their proinflammatory and growth regulatory roles through interaction with serpentine receptors. One such receptor, CXCR2, binds multiple CXC chemokines, including interleukin 8, GRO-alpha,, CRO-beta, GRO-gamma, and NAP-2, We have previously identified CXCR2 expression on myeloid cells, notably mature granulocytes, and projection neurons. Objective.-To determine the expression of CXCR2 by cells of the neuroendocrine system. Design,Archival specimens from normal neuroendocrine tissues and their malignant counterparts were analyzed by immunohistochemistry with monoclonal antibodies specific for CXCR1 and CXCR2. Results-Immunohistochemical analysis revealed high-level expression of CXCR2 by cells in the pituitary, adrenal medulla, pancreatic islets, thyroid C cells, scattered Kulchitsky cells in the bronchi, and counterpart neuroendocrine cells in the stomach, small bowel, colon, and appendix. Neuroendocrine neoplasms that demonstrated high-level CXCR2 expression included (1) primary carcinoids localized to the stomach, small bowel, colon, appendix, fallopian tube, ovary, and lung; (2) atypical carcinoids of the lung; (3) metastatic carcinoids; (4) pituitary adenomas; (5) pheochromocytomas; and (6) medullary carcinomas of the thyroid. Small cell lung carcinomas, large cell neuroendocrine carcinomas of the lung, small cell carcinoma of the cervix, Merkel cell carcinomas, neuroblastomas, and malignant melanomas lacked evidence of CXCR2 expression. Conclusions-The expression of CXCR2 by normal neuroendocrine cells and neoplastic counterparts that have retained phenotypic features of this differentiation program suggests that chemokines may play an important role in functions that are characteristic of this cell type. In addition, this raises the possibility that chemokines may modulate secretion of biologically active products of these cells and their neoplastic counterparts.
Keywords: NEURON-SPECIFIC ENOLASE; I CHROMOGRANIN-B; ENDOCRINE CELLS; INTERLEUKIN-8 FAMILY; TUMORS; LUNG; SYNAPTOPHYSIN; TISSUES; ANGIOGENESIS; NEUTROPHIL